2013
DOI: 10.1038/nm.3286
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p300 impairs Foxp3+ T regulatory cell function and promotes antitumor immunity

Abstract: Foxp3+ T-regulatory (Treg) cells maintain immune homeostasis and limit autoimmunity, but can also curtail host immune responses to various types of tumors1,2. Foxp3+ Tregs are therefore considered promising targets to enhance anti-tumor immunity, and efforts are underway to develop approaches for their therapeutic modulation. However, while studies showing that Foxp3+ Treg depletion experimentally can enhance anti-tumor responses provide proof-of-principle, they lack clear translational potential and have vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(191 citation statements)
references
References 31 publications
6
181
0
Order By: Relevance
“…Thus, pan-histone/protein deacetylase inhibitors (pan-HDACi) increase FOXP3 acetylation and DNA binding, enhance Treg production and suppressive activity, and have beneficial effects in the prevention and treatment of autoimmune disease and transplant rejection (10). Conversely, targeting of the histone acetyltransferase p300 can impair FOXP3 acetylation and Treg function while preserving T effector cell (Teff) responses and thereby promote immune responses in tumor-bearing hosts (11).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pan-histone/protein deacetylase inhibitors (pan-HDACi) increase FOXP3 acetylation and DNA binding, enhance Treg production and suppressive activity, and have beneficial effects in the prevention and treatment of autoimmune disease and transplant rejection (10). Conversely, targeting of the histone acetyltransferase p300 can impair FOXP3 acetylation and Treg function while preserving T effector cell (Teff) responses and thereby promote immune responses in tumor-bearing hosts (11).…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, such targeting strategies could have dual effects by directly impeding the cancer cells and by modulating the antitumour immune response 189 . Inhibiting the activity of HATs globally has selective effects on T Reg cell plasticity, driving T Reg cells to lose FOXP3 expression and gain IL-17 production, and probably accounts for the improved antitumour immune responses observed with this approach 141,190 . Alternatively, blocking the interactions of bromodomain-containing proteins with acetylated histones through the use of BET inhibitors (bromo domain and extraterminal inhibitors) reduces the severity of autoimmune disease in mouse models of multiple sclerosis and type 1 diabetes by broadly skewing immunity towards regulatory phenotypes 191,192 .…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…57 In vivo data also confirmed that a p300 specific inhibitor could decrease FOXP3 acetylation and Treg cell activity in mice. 75 On the other hand, two lysine deacetylases, HDAC9 and SIRT1, can associate to FOXP3, and downregulates FOXP3 acetylation level and Treg activity, where knockdown of HDAC9 or SIRT1 has been shown to enhance Treg suppressive function in vitro. 76,77 Proteins with Lysine-48 (K48)-linked poly-ubiquitination may undergo proteasome-mediated degradation.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
“…A PIM1-specific inhibitor could potentially be used to enhance the immunosuppressive activity of Treg cells through downregulating the phosphorylation of FOXP3-Ser422 during ex vivo preparation of Treg cells, 54 while PP1-specific inhibitor may work reversely and weaken the immunosuppressive activity of Treg cells; 60 STUB1-specific inhibitors, may stabilize Treg cells through preventing FOXP3 ubiquitination and degradation, whereas USP7-specific inhibitor treated Treg cells may lose their stability through promoting the process; 31,55 SIRT1/HDAC9 inhibitors would enhance the activity of Treg cells through promoting FOXP3 acetylation and facilitating its stability or activity upregulation, while P300/TIP60 inhibitors may abolish the process and promote FOXP3 degradation mediated by FOXP3 ubiquitination. 53,57,75,76 Along with the accumulation of our knowledge on the molecular mechanism of Treg immunosuppressive activity, we expect that in the next few years, increasingly safe and effective compounds, which could aid the ex vivo expansion of Treg cells by helping to maintain their stable function in vivo, will be identified and advance into clinical trials for the treatment of autoimmune diseases and other inflammatory diseases.…”
Section: Perspective and Implicationsmentioning
confidence: 99%